Study of the Administrative Barriers Influence on the Small Innovative Enterprises Activity of the RAS Institutes - S. A. Pimonova; O. A. Chudaikina (Управленческие науки, 2019)
The problem of inefficient activity of small innovative enterprises (SIE) is one of the reasons for the slow development of scientific institutions, including the RAS institutes. The state is gradually reducing their funding, forcing the management of institutions to seek the commercialization of the created intellectual property (IP). Many factors influence the activities of SIEs, such as legislative, personnel, financial, infrastructure, information and others, but administrative barriers are among the most significant. Within the framework of this study, the influence of each administrative factor on the activities of existing spin-off companies of RAS institutes is being studied. Among the main tasks of this work, a detailed analysis of Russian and foreign literature on the topic of research, the study of administrative barriers, as well as carrying an expert survey of the RAS institutes representatives in order to identify the most significant factors for the activities of SIEs can be mentioned. An expert poll was conducted by phone with a preliminarily prepared list of questions. Based on the results of the study, it can be concluded that it is exactly regulatory barriers, which require the most attention. This area demands to develop a measure set to improve their effectiveness. An important risk factor is the intellectual property weak protection, which not only deprives innovation of the opportunity to be realized, but also contributes to the leakage of technology. This problem is proposed to be solved by introducing a procedure for preliminary patent applications. In addition, it is important to continuously improve the level of knowledge in the field of patenting, intellectual property rights and entrepreneurship by research organizations. The abovementioned methods are only part of a large set of measures to reduce some of the administrative barriers in the process of commercializing innovation.